Proceedings of the 2020 ACM/IEEE International Conference on Human-Robot Interaction 2020
DOI: 10.1145/3319502.3374819
|View full text |Cite
|
Sign up to set email alerts
|

Interacting with a Social Robot Affects Visual Perception of Space

Abstract: Human partners are very effective at coordinating in space and time. Such ability is particular remarkable considering that visual perception of space is a complex inferential process, which is affected by individual prior experience (e.g. the history of previous stimuli). As a result, two partners might perceive differently the same stimulus. Yet, they find a way to align their perception, as demonstrated by the high degree of coordination observed in sports or even in everyday gestures as shaking hands. Robo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 31 publications
5
44
0
Order By: Relevance
“…Even so, the mere intervention of a seemingly social humanoid assistant had an impact on participants' training. This expands to the context of learning previous results obtained in the perceptual domain, where the mere exhibition of social behavior by a humanoid robot had a significant impact on the human partner's perception [26]. Then, we expect that endowing the robot with the possibility to adapt its social response to the partner's status will increase dramatically the effect of the robot tutoring on participants' experience.…”
Section: Discussionsupporting
confidence: 66%
“…Even so, the mere intervention of a seemingly social humanoid assistant had an impact on participants' training. This expands to the context of learning previous results obtained in the perceptual domain, where the mere exhibition of social behavior by a humanoid robot had a significant impact on the human partner's perception [26]. Then, we expect that endowing the robot with the possibility to adapt its social response to the partner's status will increase dramatically the effect of the robot tutoring on participants' experience.…”
Section: Discussionsupporting
confidence: 66%
“…Central tendency, also known as context dependency or regression to the mean [10], is a well-known perceptual phenomenon revealing the use of prior experience in perception and refers to the human tendency to generalize their perceptual judgments towards the mean of the previously perceived stimuli. This phenomenon has been recently explored in the field of visual and auditory perception of time intervals [9,11,12,13] and spatial distances [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that central tendency is dependent on the developmental stage of a person [14,12]. Interestingly, however, it also has been demonstrated that the extent to which humans generalize towards the mean can change rapidly depending to the context, such as whether a person is completing the task alone or together with another agent [15]. In particular, when interacting with a social human-like robot, participants exhibited lower central tendency and produced sensory stimuli more accurately than when they interacted with the same robot behaving mechanically, and than when they performed the task by themselves [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations